Analysis of the Role of the Karo Ethnic Young Generation in Preserving the Karo Language Amid the Challenges of Modernity - Ningsih, Claudia Ratna; Sitorus, Irma Yanti; Tarigan, Najla Haifa Maulidina; Malau, Yasinta Theresya Claudia; Lubis, Fitriani (CV. Rayyan Dwi Bharata, 2024)
This research aims to analyze the role of the young generation of Karo ethnicity in preserving the Karo language, especially amidst the challenges of modernity. The Karo language, as part of the cultural identity of the Karo ethnic group, is experiencing a shift in usage among the younger generation due to the influence of modernization, urbanization and the dominance of national and international languages. This research uses a qualitative approach with a literature study method, which utilizes various written sources such as scientific journals and academic articles. Through this method, researchers examine the factors that influence the awareness, attitudes and actions of the younger generation in preserving the Karo language. The research results show that although the younger generation's awareness of the importance of the Karo language is quite high, the practice of using this language is still limited. The main challenges faced include the dominance of Indonesian and foreign languages, lack of support from family, and the influence of digital technology. However, with the right strategy, such as the integration of formal and informal education and the use of digital media, efforts can be made to preserve the Karo language. It is hoped that this research can contribute to the development of local language preservation policies, including the Karo language.